A Note on economic growth with subsistence consumption - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
It is well known that the performance of simple models of economic growth improves substantially through the introduction of subsistence consumption. How to compute subsistence needs, however, is a difficult and controversially discussed issue. Here, I reconsider the linear (Ak) growth model with subsistence consumption and show that the evolution of savings rates and economic growth rates over time is independent from the size of subsistence needs. The model is thus more general and less subject to arbitrariness than it might have been thought initially. Quantitatively, it is shown that, although there is no degree of freedom to manipulate transitional dynamics, the model approximates the historical evolution of savings rates and growth rates reasonably well.
Keywords: O11; O41; D90; 330; Economic growth; saving; subsistence needs